Finite element analysis of a repaired cracked aluminium plate with piezoelectric patches under mechanical and thermal loading - Abdulla, Mohammed; Hrairi, Meftah; Aabid, Abdul; Abdullah, Nur Azam (Semarak Ilmu Publishing, 2025)
In thin plate structures, the use of piezoelectric actuators for active repairs can significantly decelerate the progression of crack damage. The prevalent mode-I fractures, wherein tension causes the opening displacement leading to failure, undermine the structural integrity required for load support. This current research endeavors to explore how piezoelectric (pzt) actuators influence the repair efficacy of fractured structures. The ANSYS software was harnessed to conduct the study, employing the finite element method. Additionally, the study delved into the repercussions of thermal heating and performed a parametric analysis to gauge their impact on the restoration efficiency of the compromised structure. The outcomes unveiled that the application of a negative electric field through the pzt actuator effectively diminishes the stress intensity factor (SIF) at the crack tip. Moreover, it was determined that thermal stresses contribute to a 57% augmentation in SIF, posing a heightened risk of structural failure. The study's deductions emphasize the desirability of utilizing a slender actuator alongside optimally adjusted adhesive thickness to attain a more pronounced reduction in SIF.